Avaliação da dor e qualidade de vida em pacientes classe II tratados com aparelhos Herbst e Powerscope - Morais, Nathaly Dias (2021)
Introduction: The aim of this study was to compare and evaluate pain and changes in quality of life during orthodontic therapy with a fixed orthodontic appliance in combination with two types of mandibular propulsion devices, one of the rigid type and one of the hybrid type. Methods: This prospective cohort study included a sample of 72 children with Class II malocclusion divided equally into 2 different groups, where participants in each group received therapy with the fixed orthodontic appliance and its respective propellants. To assess quality of life, participants answered the Child Perceptions Questionnaire (CPQ11-14) and to assess pain, they answered the Visual Analogue Scale (VAS). In the Herbst group, the CPQ11-14 questionnaire was applied in 3 stages: before the start of treatment (T0), three months after the installation of the propellant (T1) and three months after the installation of the fixed appliance (T2). The same group responded to the VAS: before the start of treatment (T0), after installing Herbst (T1) and after installing the .019 ”x.025” SS (T2) arch. In the PowerScope group, the questionnaire was also applied in 3 stages: before treatment (T0), three months after the installation of the fixed device (T1) and three months after the installation of the PowerScope (T2). In this group, the VAS was answered before the start of treatment (T0), after the installation of the .019 ”x.025” SS (T1) arch and when installing the mandibular propellant (T2). Results: For analysis of the data collected through the VAS, the Wilcoxon Mann-Whitney Independent test showed a reduction in the perception of pain between the 1st and the 15th day after the beginning of treatment, regardless of the type of device used. For analysis of the data collected through CPQ11-14, the Wilcoxon Mannxii Whitney Independent test and the Friedman test were applied. In the Herbst group (T1 to T2), there was a worsening in the “functional limitations” domain and, in the PowerScope group (T0 to T2), there was an improvement in the “emotional well-being” domain. In the comparison between the two groups, a difference was observed only in the “oral symptoms” domain, indicating that patients in the Herbst group have worsening in this domain when compared to patients in the PowerScope group. However, the differences observed in these domains did not influence the overall score of CPQ11-14. Conclusions: Both propulsion devices did not interfere in the perception of pain and in the quality of life of the patients in this study during the treatment of Class II malocclusion.